2005
DOI: 10.1089/jpm.2005.8.273
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Needs of Cancer Patients in U.S. Nursing Homes

Abstract: Our findings suggest important opportunities to improve the quality of cancer care for older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 22 publications
4
54
0
Order By: Relevance
“…Previous research also found that nursing home residents were less likely to have received palliative radiation and a medical oncology consultation in the last months of life [16,23,39,41]. Reasons why nursing home residents are not receiving the same level of oncology services as those who do not reside in nursing homes need to be studied further.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Previous research also found that nursing home residents were less likely to have received palliative radiation and a medical oncology consultation in the last months of life [16,23,39,41]. Reasons why nursing home residents are not receiving the same level of oncology services as those who do not reside in nursing homes need to be studied further.…”
Section: Discussionmentioning
confidence: 96%
“…Only 4.8% of nursing home residents with cancer were noted to be obtaining hospice services, with the percentage rising to 11% among those terminally ill [23].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations